PENERAPAN NILAI-NILAI PENDIDIKAN ISLAM DALAM PELAKSANAAN KURSUS PRA NIKAH UNTUK MEWUJUDKAN KELUARGA SAKINAH - Lutfi Kusuma Dewi (Universitas Islam Sultan Agung, 2019)
The birth of the Regulation of Dirjen Bimas Islam No. DJ. 491/11 of 2009 concerning Course for the Brides, which was then refined by the Regulation of Dirjen Bimas Islam No. DJ.II / 542 of 2013 concerning the Guidelines for Implementing the Pre-Marriage Course is a government effort in providing knowledge, understanding, and skills for brides. With this provision, it is expected to be able to reduce divorce rates and anticipate other various family problems. In practice, this pre-marriage course program faced various obstacles so that it was considered to be less optimal. This article examines various problems that occur in the field surrounding the implementation of pre-marital courses and offered some Islamic education values as solutions. Regulations, socialization, legitimacy, and collaboration between institutions are needed so that the pre-marital course has a strong bargaining position and the implementation will be more optimal and functional.Keywords: Pre-Marital Courses, Sakinah Family, Islamic Value